Restorative Justice for Blasphemy in Indonesia: Study on the Application of the PNPM Law No. 1 of 1965 - Eva Achjani Zulfa (International Journal of Science and Society, 2019)
As is known, the issue of blasphemy in Indonesia became sticking out and rife after the Al Maidah 51 blasphemy case committed by former DKI Jakarta Governor Basuki Tjahaya Purnama or better known to Ahok, continued with event 212 which became an essential moment in the development of the case other blasphemy cases. The concern is how relevant institutions and the ministry of religion are government representatives react in handling these cases. Because in reality, all these cases always end up in prison. Is this the right solution. This study aims to analyze the role of restorative justice in the handling of blasphemy cases in Indonesia. This research uses a qualitative approach with the literature study method in analyzing this problem.